Bias‐Free Graphene Solid Cell to Realize the Real‐Time Observation on Dynamical Changes of Electrodes. Issue 2 (30th November 2022) - Cheong, Jun Young; Chang, Joon Ha; Choe, Jacob; Yuk, Jong Min; Kim, Il‐Doo
Abstract: To realize the development of high‐performance electrodes materials, real‐time observation tool that can visualize dynamical changes of electrode materials upon lithiation and sodiation is highly critical. Recently, in situ transmission electron microscopy (TEM) has gained much attraction as it provides rich information on both phase and morphological transitions of electrode materials upon lithiation and sodiation in an atomic scale. Nevertheless, two significant limitations are present for current in situ TEM study: i) most of the in situ TEM experiments use a specially designed TEM holder, which is costly and suitable for use in only selective types of TEM; and ii) recently developed in situ TEM techniques with no applied bias have inherent limitations in the size of the sample (difficult for a size above 50 nm). Overcoming these two aforementioned issues, bias‐free graphene solid cells (GSCs) are now introduced, which can conduct real‐time observation of electrode materials in any size dimensions and morphologies without using bias. In this work, dynamical changes of hollow SnO2 nanotubes (NTs) are visualized upon lithiation and sodiation in real time using GSCs, where rich information is obtained on the morphology‐dependent, ion‐dependent characteristics of dynamical changes. Abstract : A novel bias‐free graphene solid cell is suggested as a cost‐effective and facile in situ transmission electron microscopy (TEM) tool to observe electrode materials. Upon e‐beam irradiation, lithium fluoride (LiF) and sodium fluoride (NaF) can be easily decomposed to trigger lithiation and sodiation, which can proceed to observe dynamical changes of electrode materials inside TEM.